Religion and psychology : mapping the terrain : contemporary dialogues, future prospects - Jonte-Pace, Diane E. (Diane Elizabeth), 1951-; Parsons, William B. (Routledge, 2001)
This work is a survey of the current state of the relationship between religion and psychology from the leading scholars in the field.